Was uns die Sprache des Rechts über die Sprache sagt = What can the language of the law tell us about language? - Klein, Wolfgang (Zeitschrift für Literaturwissenschaft und Linguistik, 2017)
Traditional as well as modern linguistics are in many ways biased by a one-sided diet of examples. Our ideas about tense, mood, definiteness and indefiniteness, to mention but these, are mainly tuned to utterances which describe singular situations in reality. In these contexts, it makes sense to say, for example, that tense relates the time of the situation to the deictic time of speech. But there are many other discourse types, for example laws and other legal texts, which do not seem to function in this way. It is difficult to see, for example, what the ›time of speech‹ in this type of texts is. Still, they use tense marking, such as the present and the perfect. A number of examples from legal texts are examined, and it is shown that standard assumptions about the functioning of tense, definiteness and other categories reflect very special cases of their meaning.